Qs Knowledge And Involvement In Heritage Building Conservation Works - Hisham, Nur Auji Athirah (2017)
From year to year, the number of heritage buildings is increasing and they need to be conserved. Conservation work is considered to be a new expansion in the construction industry, thus the QS experience and knowledge in conservation projects are still lacking. Consequently, the industry is currently faced with ill-prepared documents that lead to cost and time overruns; and contractual disputes during the post-contract stage.